Commonly Used Anesthesia/Euthanasia Methods for Brain Collection Differentially Impact MAPK Activity in Male and Female C57BL/6 Mice - Ko, Mee Jung; Mulia, Grace E.; van Rijn, Richard M. (Frontiers in Cellular Neuroscience, 2019)
The mitogen-activated protein kinases (MAPK) are a family of protein kinases that regulate crucial neuronal functions such as neuronal differentiation, proliferation, and apoptosis through phosphorylation of subsequent protein kinases. The three classical MAPK subfamilies, extracellular signal-regulated kinase 1 and 2 (ERK1/2), C-Jun N-terminal kinase (JNK), and p38 kinase have been linked to various neurological disorders often in conjunction with activation of a wide range of G-protein coupled receptors and receptor tyrosine kinases. Many studies investigating MAPK function in these disorders rely on histochemistry or immunoblotting that require brain isolation following euthanasia. Here, we evaluated to what degree different modes of anesthesia/euthanasia impact MAPK activity in adult male and female C57BL/6 mice. Mice were decapitated following ketamine/xylazine or isoflurane anesthesia, carbon dioxide asphyxiation, or without anesthesia. We selectively chose five brain regions (the prefrontal cortex, the hippocampus, the striatum, the nucleus accumbens, and the amygdala) that are heavily implicated in neuropsychiatric disorders. We found that relative to carbon dioxide asphyxiation, the other methods displayed significantly stronger ERK1/2 phosphorylation in select brain regions of male and female mice, with sex differences for a couple of regions. A similar yet less pronounced trend was observed for JNK activity, whereas the choice of euthanasia method did not differentially impact p38 phosphorylation. Our study results reveal how small differences in experimental design may impact whether one will be able to detect drug- or disease-related changes in MAPK activity. These findings are timely in a period where experimental rigor is emphasized to increase reproducibility of research.